Anthracotheres from Wadi Moghra, Early Miocene, Egypt. (September 2014) - Miller, Ellen R.; Gunnell, Gregg F.; Gawad, Mohamed Abdel; Hamdan, Mohamed; El-Barkooky, Ahmed N.; Clementz, Mark T.; Hassan, Safiya M.
Abstract : The early Miocene site of Wadi Moghra, Qattara Depression, Egypt, is important for interpreting anthracothere (Mammalia, Artiodactyla) evolution, because the Moghra sediments preserve a higher diversity of anthracotheres than any other pene-contemporaneous site. New specimens from Moghra are described and form the basis for the systematic revision of Moghra anthracotheres provided here. Among the important discoveries recently made at Moghra is the first complete skull of Sivameryx moneyi . Other new specimens described here include two new species of Afromeryx, and a new genus and species, all of which are unique to Moghra. A review of biogeographic information supports the conclusion that three of the Moghra anthracotheres ( Brachyodus depereti, B. mogharensis, and Jaggermeryx naida, n. gen. n. sp.) are members of late surviving lineages with a long history in Africa, while three other species ( Afromeryx grex, n. sp., A. palustris, n. sp., and Sivameryx moneyi ) represent more recent immigrants from Eurasia.